Carbon–carbon bond activation of cyclobutenones enabled by the addition of chiral organocatalyst to ketone - Li, Bao-Sheng (2018)
The activation of carbon–carbon (C–C) bonds is an effective strategy in building functional molecules. The C–C bond activation is typically accomplished via metal catalysis, with which high levels of enantioselectivity are difficult to achieve due to high reactivity of metal catalysts and the metal-bound intermediates. It remains largely unexplored to use organocatalysis for C–C bond activation. Here we describe an organocatalytic activation of C–C bonds through the addition of an NHC to a ketone moiety that initiates a C–C single bond cleavage as a key step to generate an NHC-bound intermediate for chemo- and stereo-selective reactions. This reaction constitutes an asymmetric functionalization of cyclobutenones using organocatalysts via a C–C bond activation process. Structurally diverse and multicyclic compounds could be obtained with high optical purities via an atom and redox economic process.